Kualitas Semen Cair Sapi Peranakan Ongole pada Pengencer Tris Aminomethan Kuning Telur tanpa Raffinosa yang Disimpan pada Media yang Berbeda Suhu - Deny Sulistyowati; Muhammad Azharil Faris; Aulia Puspita Anugra Yekti; Sri Wahjuningsih; Trinil Susilawati (TERNAK TROPIKA Journal of Tropical Animal Production, 2018)
The aim of this research was to know the storage media with the best temperature to maintain the quality of Ongole crossbred bull liquid semen diluted with tris aminomethan without raffinose + 20% egg yolk. The material used in this research was semen obtained from Ongole crossbred bull located in Sumber Sekar Laboratory of Faculty of Animal Husbandry Universitas Brawijaya Malang. The method was used in laboratory experimental research with experimental design used 5 treatments with 5 replications, there were M1 (thermos containing ice cubes with temperature 0o C), M2 (refrigerator temperature 3-5o C), M3 (thermos containing ice water with temperature 9o C), M4 (thermos containing water with temperature 25o C), and M5 (empty thermos with temperature 28o C). The variables observed were motility, viability, abnormality, and total motile sperm. Data were analyzed using Randomized Block Design, total motile sperm tested using Pearson's Chi Square with expectation value of 40 million motile sperm/ml. The result of this research showed that the storage media had a significant effect on the quality of Ongole crossbred bull liquid semen of motility, viability, and abnormality. Total motile sperm at the 3rd hour showed significantly different M3 and M4 (P <0.05) lower than the expected value of 40 million motile sperm/ml. The conclusion of the research shows that M1 (flask containing ice cubes with temperature 0o C) was the best storage media to carry liquid semen for artificial insemination application in the field.